Pengaruh Media Jam Pecahan terhadap Hasil Belajar Materi Pecahan pada Siswa Kelas V Madrasah Ibtidaiyah Ma’had Al-Zaytun - Showatul Dini; Irvan Iswandi; Dewi Utami (Realisasi : Ilmu Pendidikan, Seni Rupa dan Desain, 2025)
The use of various instructional media plays a significant role in the teaching process, as it can stimulate students' interest and encourage active participation in learning activities. By utilizing a variety of educational tools, children can enhance the efficiency of their learning in relation to the material delivered by the teacher. Teachers are expected to select the most effective teaching models, instructional media, and strategies to improve students' understanding. The use of instructional aids such as fraction clocks can serve as an innovative resource for teachers in presenting learning materials. Through the implementation of such media, teachers can expand the scope of media utilization in the educational process. The use of fraction clocks aims to inspire and improve students’ learning outcomes in the field of mathematics. The study employs a quantitative approach. This quasi-experimental study applies a Pretest-Posttest Control Group design. 50 students participated in the study. The collected data are analyzed using descriptive statistical techniques to describe the students’ pretest and posttest results. Furthermore, inferential statistics, including normality tests and hypothesis testing, are used to support further interpretation. The findings revealed that for the pretest, students had an average score of 51.92, indicating a moderate level of achievement, with a percentage of 62%. And the students’ postest scores increased to 66.92, indicating a higher level of achievement, with a percentage of 69% based on a sample of 26 students. The Paired Sample T-test showed a Sig. (2-tailed) value of 0.000, which is lower than the predetermined significance level of 5% or 0.05. This indicates the rejection of null hypothesis and acceptance of alternative hypothesis. It can be concluded that the use of fraction clock as an instructional medium has positive effect on students’ learning outcomes and enhances their understanding of fraction concepts.